Determinants of binge eating and its impact on indicators of obesity among Finnish adolescents - a cohort study - Reetta Lehto; Monica Ålgars; Sohvi Lommi; Marja H Leppänen; Heli Viljakainen (Journal of Eating Disorders, 2024)
Abstract Background Binge eating, a type of disordered eating, is relatively common among youth and predisposes them to many adverse health outcomes. Diverse psychological and social factors may be associated with binge eating. The aim of this study was to examine child and parental psychosocial determinants of binge eating and its impact on indicators of obesity. Methods The sample consisted of 10 679 Finnish adolescents who participated in the Fin-HIT cohort study. The participants were 9–12 years at baseline, and they were followed-up for 2.6 years on average. At baseline, children’s anthropometry was measured, and they reported binge eating, disordered eating attitudes and behaviors, self-esteem, and body shape satisfaction with validated questionnaires. Parents reported their own weight satisfaction, dieting, and depressive symptoms at baseline. Adjusted logistic and linear regressions were used in the analyses. Results Self-esteem was associated with lower odds (OR 0.88, 95% CI 0.85–0.91), and overall disordered eating attitudes and behaviors were associated with higher odds (OR 1.08, 95% CI 1.06–1.10) of binge eating. Additionally, child and parent body dissatisfaction were associated with binge eating but not in the fully adjusted model where the child’s BMI was additionally considered. None of the parental factors were associated with binge eating in the fully adjusted model. Binge eating was associated with higher BMI z-scores and waist circumferences both cross-sectionally and longitudinally. Conclusions In support of previous findings, we found that low self-esteem, body dissatisfaction and other disordered eating attitudes and behaviors are associated with binge eating, but our results also highlight the impact of weight status as a potential moderator when the determinants of binge eating are examined. More studies on the role of parental factors in adolescent binge eating are needed.